A web application dashboard: an application of bibliometric analysis of zakat / Ashraff Ruslan - Ruslan, Ashraff (Universiti Teknologi MARA, Negeri Sembilan, 2023)
In general, displaying Bibliometric Analysis of Zakat results as a dashboard is difficult for researchers, especially when certain graph outputs cannot be included due to limited technical knowledge and the limited type of charts available in the market. This web application displays Bibliometric analysis with the Biblioshiny web application from R programming. Bibliometric analysis, including several charts, is used to visualize the science mapping. One of the major benefits is for non-coders which the researcher can create an interactive dashboard utilizing an open-source dashboard platform without having to go through a hassle in coding to perform bibliometric Analysis. Researchers will also benefit from Diversity: which can display results through interactive charts and visuals, Rapid prototyping: which can reuse the dashboard for another subject and parameters, Design: sophisticated graphic capabilities can be created, and Structured: having a clear framework of analysis and the results can be added into report compilation and be downloaded in single Excel document with different sheets according to analysis flow.